PENERIMAAN IBU – IBU MUSLIM TERHADAP IMUNISASI MEASLES RUBELLA PADA BALITA DI KAMPUNG JAWA WANASARI, KOTA DENPASAR - Swandari, Ni Luh Putu Indah; Kardiwinata, Made Pasek (ARCHIVE OF COMMUNITY HEALTH; Vol 6 No 2 (2019): Desember 2019, 2019)
ABSTRACT Bali Province has successfully conducted a Measles Rubella (MR) immunization campaign with coverage above national target (97.96%). There have been pros and cons of the Muslim community. It was, because of there was no halal MR vaccine from their perspektif. Mothers as parents have a important role in immunization. The purpose of this study was to determine the acceptance of Muslim mothers to vaccinate their under five years old children in Kampung Jawa Wanasari, Denpasar City. This study used a descriptive cross sectional design. Samples in this study were Muslim mothers who had under five years old children. This study used simple random sampling as sampling technique. Mothers who received MR immunization for their children are 77.63%. Mothers mostly feel the high benefits of MR immunization (81.58%). The barrier in vaccination were low (63.16%). Mothers received high support for MR vaccination from family (81.58%), health workers (84.21%) and religious leaders (69.74%). Acceptance of MR immunization in Kampung Jawa Wanasari classified low and under national target. Key Word : Acceptance, Muslim, Immunization